Characteristics of a Danish football talent development environment - A constructivist case study of FCK School of Excellence - Vestergaard Jensen, J.; Smith Clementsen, P. (2016)
The purpose of this thesis is to identify characteristics of a Danish football talent development environment in regards to the U15 and U17 teams, including the social processes and interactions between different components and how these contribute to talent development. This results in the following problem statement: "What characterises the talent development environment in FCK School of Excellence in regards to the U15 and U17 teams? The theoretical framework is primarily based on a holistic ecological approach (Henriksen, 2010), based on system theory and cultural psychology, applying two working models: The Athletic Talent Development Environment (ATDE) model and an adapted version of the Environment Success Factors (ESF) model. The method includes a constructivist case study design, including observations in the field, four semi-structured interviews and document analysis. The findings revealed that the talent development environment under study is characterised by having a large budget as well as by the athletic domain setting the agenda. Location is seen as both a resource and a barrier, while there is a great deal of organisational curiosity and a strong belief in doing things "our way". There is a firm structure and strong leadership in the club, which focusses on educating the individual player, as well as the whole person. Moreover, there is a clear separation between U15 and U17 in regards to organisational structure, while there is a close cooperation between club, school and parents, which is gradually decreasing from U15 to U17. Additionally, the club has many full time employees such as coaches and various experts. In conclusion, the findings highlight that talent development, in general in this particular case, is highly contextual and a dynamic process, which requires awareness of an inherent complexity where coaches and talent development environments have to adapt to these contextual demands.